5-(2u-1)=14-4u

Simple and best practice solution for 5-(2u-1)=14-4u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-(2u-1)=14-4u equation:


Simplifying
5 + -1(2u + -1) = 14 + -4u

Reorder the terms:
5 + -1(-1 + 2u) = 14 + -4u
5 + (-1 * -1 + 2u * -1) = 14 + -4u
5 + (1 + -2u) = 14 + -4u

Combine like terms: 5 + 1 = 6
6 + -2u = 14 + -4u

Solving
6 + -2u = 14 + -4u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '4u' to each side of the equation.
6 + -2u + 4u = 14 + -4u + 4u

Combine like terms: -2u + 4u = 2u
6 + 2u = 14 + -4u + 4u

Combine like terms: -4u + 4u = 0
6 + 2u = 14 + 0
6 + 2u = 14

Add '-6' to each side of the equation.
6 + -6 + 2u = 14 + -6

Combine like terms: 6 + -6 = 0
0 + 2u = 14 + -6
2u = 14 + -6

Combine like terms: 14 + -6 = 8
2u = 8

Divide each side by '2'.
u = 4

Simplifying
u = 4

See similar equations:

| x*2-2x=0 | | 3x-19=x-2 | | 2.23-3.14x=2x-4.195 | | 2(4x+3)=2 | | 4x-15=x+10 | | 5x-12=2x-9 | | 2H+4S=22 | | 5(x-3)=-13 | | 19-x+4+x+19+x-1=34 | | 3x=1.08 | | F(x)=(radx-2)-3 | | ln(3-7x)=-2 | | 3x+1.66=1.8 | | 10x^3+58x^2+43x-11=0 | | 10x^3+58x^2+43x-11=f(x) | | 24x=-16x^2+6 | | 5x-7y=29 | | 5cos(x)=0 | | 0.04*0.8= | | x+(2x+15)=150 | | 0.75d-0.67d=0.67+6 | | 88+5x= | | K-(-6)=-33 | | x+0.5x+0.25x+1=100 | | x+(2x-15)=150 | | x+0.5x+0.75x+1=100 | | 6x-2=64(2x) | | 5+2+x=9 | | 4x=12-x | | sin*2*t= | | 3y+3=6(y+1) | | (2x+5)+(2x+2)=4(x-1)+9 |

Equations solver categories